Evaluation of frequency of antibodies against toxoplasma gondii, neospora caninum and Sarcocystis spp. and transmission routes in sheep from Humid Pampa, Argentina - Hecker, Yanina Paola (2018)
The aim of this study was to describe the frequency of ovine specific antibodies to Toxoplasma gondii, Neospora caninum and Sarcocystis spp. and to estimate different transmission routes of these infections. One hundred and thirty Texel sheep and their 117 Texel lambs were included in the study. Serum samples were tested for antibodies to T. gondii, N. caninum and Sarcocystis spp. using IFAT. Toxoplasma gondii seroprevalence was 10.00% in sheep (IC95%: 4.80–15.20%), being higher in adult sheep (≥12 year) than in younger sheep (OR 1.30; 95% CI, 1.10–1.50). N. caninum and Sarcocystis spp. seroprevalences were 1.54% (IC95%: 0.00–5.70) and 72.09% (IC95%: 67.70–82.70), respectively, with no association between age and seropositivity in sheep (P>0.05). T. gondii seroprevalence in lambs was 4.27% (IC95%: 0.61–7.94). No association between T. gondii serological status in sheep and their lambs was detected (P = 0.07). Two T. gondii and Sarcocystis spp. seropositive lambs were euthanized and T. gondii and Sarcocystis spp. DNA was detected by PCR in their tissues. In conclusion, the increase of T. gondii seropositivity in relationship with sheep age and the lack of association between sheep-lamb serological status, suggest that horizontal infection is the main transmission route in this flock as reported before. Due to the low number of N. caninum-seropositive ewes no assumptions can be done about the impact of this parasite in this flock. According with previous reports, the main transmission route for Sarcocystis spp. in this species in the present study was horizontal.